MENYIASATI KETIMPANGAN DI BIDANG ANTARA DUNIA PENDIDIKAN KEJURUAN DAN DUNIA INDUSTRI - ., Asmungi; Kusnanto, Geri (Heuristic, 2016)
The rapid development of CNC machine technology, often makes the inequality of knowledge between the world of vocational education (SMK) and the world of industry. Along with the development of computer technology is so fast, now born as CNC machines with the latest generation Mitsubishi-based, Fanuc-based, or GSK-based operating system. Meanwhile in the world of education is still using EMCO-based. Not easy for SMK to follow developments. Financial constraints is one of classic factors. This study tries to deal with this inequality without being affected by financial constraints, namely by replacing the engine-based laboratory with a simulator-based laboratory. To test whether this simulator is able to overcome inequality, then the treatment of the two groups were paired consisting of teachers and students. By testing the hypothesis Ho: Î¼ 1 -Î¼ 2 = 0, and by using a Likert index analysis known that the CNC simulator is able to replace the actual existence of a CNC machine. It mean that inequality can be solved immediately. Keywords: inequality, CNC machining , vocational education, CNC simulator